MAKNA RITUAL TOLAK BALA DI AIR TERJUN SEDUDO PADA MASYARAKAT DESA NGLIMAN NGANJUK - Al-Ghifari, M. Abu Dzar; Handoyo, Pambudi (UHN IGB Sugriwa Denpasar, 2024)
This article investigates the meaning and role of the ritual of rejecting reinforcements at Sedudo Waterfall in the lives of the people of Ngliman Village, especially in the context of efforts to prevent and reject reinforcements or disasters that are considered to threaten their lives. This research uses a qualitative approach with literature review techniques to deepen understanding of the significance of the ritual. The research results show that the ritual of rejecting reinforcements at Sedudo Waterfall is not just a tradition passed down from generation to generation, but also contains deep spiritual, social and cultural meaning. People involve themselves in this ritual as a form of expression of belief in supernatural powers which are believed to be able to maintain prosperity and harmony in their lives. Apart from that, this ritual is also an important moment to strengthen social solidarity and cultural identity among the residents of Ngliman Village. This article presents a holistic picture of how the ritual of rejecting reinforcements at Sedudo Waterfall not only plays a role as a religious practice, but also as a means of building and maintaining togetherness in the Ngliman Village community.